Effect of mini-screw-facilitated micro-osteoperforation on the rate of orthodontic tooth movement: a single-center, split-mouth, randomized, controlled trial - Neda Babanouri; Shabnam Ajami; Parisa Salehi (SpringerOpen, 2020)
Abstract Objective The present study aimed to evaluate the effect of MOP over a 3-month period and to determine the influence of the number of perforations on the rate of canine retraction. In addition, the amount of pain and discomfort caused by the MOP method was evaluated. Trial design A single-center, split-mouth, triple-blind, randomized, controlled trial was conducted. Methods The clinical trial was conducted from December 2018 to July 2019 in the Orthodontic Clinic, Shiraz Dental School. Twenty-eight patients (range from16.3 to 35.2 years) who need fixed orthodontic treatment were recruited and randomly assigned to MOP1 and MOP2 groups. In each patient one side of the mouth worked as a control side which received no MOPs. Four months after first premolars extraction, patients in MOP1 group received 3 MOPs on the buccal surface of alveolar bone in the experimental side to accelerate canine retraction whereas patients in MOP2 group received 3 buccal MOPs and 3 palatal MOPs in the experimental side. The amount of canine retraction was measured every 28 days at three intervals on both sides of the mouth. Pain perception was also measured on the day of MOP procedure and subsequently at 24 h. Randomization was performed using online software RANDOM.ORG; the recruited patients were divided into two parallel groups with a 1:1 allocation ratio then the side of MOPs intervention in each subject was randomly determined with coin tossing. Triple blinding design was employed. Results The result of the intra-examiner reliability using ICC was 0.97 (P <  0.001), indicating excellent repeatability and reliability of the measurements. The baseline characteristics between the groups were similar (P > 0.05). There was a significant difference in the rate of canine retraction between the MOP groups and the contralateral control sides, as well as between the MOP1 and MOP2 groups (P <  0.05). Conclusion The MOP procedure was effective in accelerating orthodontic tooth movement, although the amount of acceleration was not clinically significant in the case of canine retraction. An increase in the number of MOPs resulted in a significant acceleration of the canine retraction. Trial registration The trial was registered 30 November 2018 at the Iranian Registry of Clinical Trials ( IRCT20181121041713N1 ).